Learning To Be New Youth Generation In Innovation And Creativity With Entrepreunership - Mahadewi, Erlina.Puspitaloka; Dihin Septyanto (CV. Inara, 2021)
The present study is for achieve also improving the education and information provided to be new young generation in entrepreunership with innovation and creativity. The Covid 19 epidemic in Indonesia in since year 2020 until today requires entrepreneurs who are strong enough to improve the economy of a country. Entrepreneurs must be able to compete and always be able to increase their productivity. One way is through creativity and innovation. The purpose of this research is to know that creativity and innovation support activities and activities of doing entrepreneurship. The research method uses qualitative research with a literature review approach, also in-depth interviews with informans where data is taken based on previous research. The results of the study prove that creativity and innovation are very helpful for entrepreneurial activities, especially during this corona or covid-19 pandemic. For new youth entrepreneurs in 2021 and the next future, the innovation and creativityare very vital basic capital to face the business world, especially in terms of very tight and competitive business competition. The conditions of very tight competition coupled with changes in the very dynamic business climate. Require entrepreneurs to always be ready to face existing obstacles and changes that are a consequence of competition and changes in the business climate, and even have to be a precursor or pioneer of change even as a benchmark also as a market leader in business competition for the youth generation now and future after pandemic.